Aplikasi Tik Tok sebagai Media Informasi Berita (Studi Kasus Karyawan Perkebunan Bungara, Kecamatan Bahorok, Langkat) - Muhammad Irfan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This article discusses the perspective of Bungara Plantation employees regarding the Tik Tok application as a news information medium. Social media is currently the choice of many peopleas a means of entertainment, communication and also news information. One of the social media that is in great demand by people from various circles is Tik Tok. Currently, Tik Tok users have experienced a significant increase compared to previous years. The Tik Tok application not only contains content about entertainment but also contains various news information. This article uses descriptive qualitative research methods. The data source was obtained from interviews with several employees of the Bungara Plantation. The results showed that the Tik Tok application as a news information medium was considered invalid and even contained a lot of hoax news. In addition, the limited and short duration of broadcasting news content is a weakness and shortcoming of the Tik Tok application.